2011
DOI: 10.1177/1538574411414304
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of Failed Autogenous Conduit Utilizing Laser Revascularization

Abstract: The traditional approach for the treatment of restenosis of autogenous vein bypass has been revision of bypass with vein patch angioplasty, interposition jump graft, or thrombectomy procedures for those patients with extensive occlusive disease and limb-threatening ischemia. Endovascular intervention traditionally involves angioplasty of the graft; however, vessels with diffuse disease or extensive longitudinal lesions are generally difficult to revascularize utilizing this technique. Surgical revision of a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Three articles described other off-label excimer laser indications in endovascular therapy. First, Chander et al [34] reported a case series of 4 recanalizations of failed autogenous saphenous vein graft using laser revascularization. A 0.9 to 1.7 TE laser catheter was used with 100% technical success.…”
Section: Off-label Indicationsmentioning
confidence: 99%
“…Three articles described other off-label excimer laser indications in endovascular therapy. First, Chander et al [34] reported a case series of 4 recanalizations of failed autogenous saphenous vein graft using laser revascularization. A 0.9 to 1.7 TE laser catheter was used with 100% technical success.…”
Section: Off-label Indicationsmentioning
confidence: 99%